Pengaruh Kualitas Pelayanan, Harga dan Lokasi Terhadap Kepuasan Pelanggan Lesehan D’dadoz (Studi Kasus pada Pelanggan Lesehan D’dadoz Kota Blitar) - Nikmatur Rosidah; N Rachma; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to test the Effect of Service Quality, Price, and Location on Lesehan D'dadoz Customer Satisfaction. The number of samples was determined using the Maholtra formula and the results of 90 respondents were obtained. The data was obtained by distributing questionnaires to customers of lesehan d'dadoz selected by purposive sampling. Data analysis in this study used SPSS version 29. The data testing techniques used in this study include validity tests, reliability tests, normality tests, classical assumption tests, multiple linear regression analysis tests, f tests, t tests and coefficient of determination (R2) tests. The results of this study show that the quality of service, price and location have a positive and significant effect on customer satisfaction Keywords: Service Quality,, Price, Location, Customer Satisfaction